2017
DOI: 10.15761/ams.1000114
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization of Cu, N co-doped TiO2 microspheres with enhanced photocatalytic activities

Abstract: The mesoporous Copper, nitrogen co-doped TiO 2 microspheres was prepared via solvothermal approach, followed by nitriding treatment under an ammonia gas flow. The crystalline structures of the as-prepared catalyst and the chemical compositions of Cu,N co-doped TiO 2 were determined using X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) respectively. The photocatalytic activity of the as-prepared sample was investigated by monitoring the degradation of Rhodamine-B under visible light irradiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…These observations notified the presence of N in NMSd and modified the phase [38] . Generally, the peak at ∼396 eV reflected the formation of N‐Metal‐S, which indicated the replacement of S ion by N ion [39] . The atomic percentage of all the prepared compositions were calculated and summarized from survey spectra analysis in supporting information (depicted in Table S1).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…These observations notified the presence of N in NMSd and modified the phase [38] . Generally, the peak at ∼396 eV reflected the formation of N‐Metal‐S, which indicated the replacement of S ion by N ion [39] . The atomic percentage of all the prepared compositions were calculated and summarized from survey spectra analysis in supporting information (depicted in Table S1).…”
Section: Resultsmentioning
confidence: 94%
“…[38] Generally, the peak at ~396 eV reflected the formation of N-Metal-S, which indicated the replacement of S ion by N ion. [39] The atomic percentage of all the prepared compositions were calculated and summarized from survey spectra analysis in supporting information (depicted in Table S1). All these elemental information obtained from the survey spectra (atomic percentage value) and deconvoluted profile analysis helped to measure the probable composition of NMSd as MoS 2-x N x (x = 0.0386), MoS 2-y N y (y = 0.0738), and MoS 2z N z (z = 0.1037), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Antimicrobial effectiveness which depends on the concentration and size displays inverse relation to the size of doped material. 27,36,38,75 Small-sized NPs generate more reactive oxygen species (ROS) which halt effectively in implants of pathogenic bacteria membrane resulting in extrusion of cytoplasmic constituents thus killing bacteria 76,77 Secondly, the strong cationic interaction of Cu ++ with negative parts of bacterial membrane results in signicant bactericidal activity at high concentrations by inducing collapse and cell lysis of bacteria (Fig. 15).…”
Section: Load Of Photocatalystmentioning
confidence: 99%
“…25 increased surface area-to-volume ratio with better light absorption in the visible spectrum and thus demonstrated the improved photocatalytic activity. 26 Likewise, Mathis et al investigated the photocatalytic activity of Cu/N-TiO 2 nanoparticles. To improve the photocatalytic activity, they suggested the preparation of monodisperse microsphere of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al reported the solvothermal preparation of mesoporous Cu/NT-TiO 2 microspheres. The prepared nanoparticles exhibited an increased surface area-to-volume ratio with better light absorption in the visible spectrum and thus demonstrated the improved photocatalytic activity . Likewise, Mathis et al investigated the photocatalytic activity of Cu/N-TiO 2 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%